Dendrogenin A and B two new steroidal alkaloids increasing neural responsiveness in the deafened guinea pig - Fransson, Anette; de Medina, Philippe; Paillasse, Michaël R.; Silvente-Poirot, Sandrine; Poirot, Marc; Ulfendahl, Mats (Frontiers in Aging Neuroscience, 2015)
Aim: To investigate the therapeutic potential for treating inner ear damage of two new steroidal alkaloid compounds, Dendrogenin A and Dendrogenin B, previously shown to be potent inductors of cell differentiation. Methods: Guinea pigs, unilaterally deafened by neomycin infusion, received a cochlear implant followed by immediate or a two-week delayed treatment with Dendrogenin A, Dendrogenin B, and, as comparison artificial perilymph and glial cell-line derived neurotrophic factor. After a 4-week treatment period the animals were sacrificed and the cochleae processed for morphological analysis. Electrically-evoked auditory brainstem responses were measured weekly throughout the experiment. Results: Following immediate or delayed Dendrogenin treatment the electrical responsiveness was significantly maintained, in a similar extent as has been shown using neurotrophic factors. Histological analysis showed that the spiral ganglion neurons density was only slightly higher than the untreated group. Conclusions: Our results suggest that Dendrogenins constitute a new class of drugs with strong potential to improve cochlear implant efficacy and to treat neuropathy/synaptopathy related hearing loss. That electrical responsiveness was maintained despite a significantly reduced neural population suggests that the efficacy of cochlear implants is more related to the functional state of the spiral ganglion neurons than merely their number.